Case report: A Chinese patient with spinocerebellar ataxia finally confirmed as Gerstmann-Sträussler-Scheinker syndrome with P102L mutation - Chen, Lin; Xu, Yin; Fang, Ming-juan; Shi, Yong-guang; Zhang, Jie; Zhang, Liang-liang; Wang, Yu; Han, Yong-zhu; Hu, Ji-yuan; Yang, Ren-min; Yu, Xu-en (Frontiers in Neurology, 2023)
Gerstmann-Sträussler-Scheinker syndrome (GSS) is a rare genetic prion disease caused by a mutation in the prion protein (PRNP) gene. It is typically characterized by progressive cerebellar ataxia and slowly progressive dementia. We present a case study of the GSS from China in which a 45-year-old male with a progressive gait and balance disorder developed cerebellar ataxia onset but was misdiagnosed as spinocerebellar ataxia (SCA) for 2 years. The patient's clinical, electrophysiological, and radiological data were retrospectively analyzed. Examination revealed ataxia, dysarthria, muscle weakness, areflexia in lower limbs, including a pyramidal sign, whereas cognitive decline was insignificant. His late mother had a similar unsteady gait. An electroencephalogram (EEG) showed normal findings, and 14-3-3 protein was negative. A brain MRI was performed for global brain atrophy and ventricular enlargement. Positron emission tomography–computed tomography (PET–CT) (18F-fluoro-2-deoxy-d-glucose, FDG) images showed mild to moderate decreased glucose metabolism in the left superior parietal lobe and left middle temporal lobe. According to genetic testing, his younger brother also had the P102L variant in the PRNP gene. This single case adds to the clinical and genetic phenotypes of GSS.